2013
DOI: 10.1371/journal.pone.0060469
|View full text |Cite
|
Sign up to set email alerts
|

The Calpain/Calpastatin System Has Opposing Roles in Growth and Metastatic Dissemination of Melanoma

Abstract: Conventional calpains are ubiquitous cysteine proteases whose activity is promoted by calcium signaling and specifically limited by calpastatin. Calpain expression has been shown to be increased in human malignant cells, but the contribution of the calpain/calpastatin system in tumorigenesis remains unclear. It may play an important role in tumor cells themselves (cell growth, migration, and a contrario cell death) and/or in tumor niche (tissue infiltration by immune cells, neo-angiogenesis). In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…[25][26][27][28][29] Indeed, expression levels of μ-calpain correlate with malignancy in renal cell carcinoma and invasiveness in hepatocellular carcinoma. 28,29 Systemic overexpression of CAST and pharmacological intervention against systemic calpain systems reportedly ameliorate allograft tumors 30 and OIR, 14 respectively; nevertheless, the mechanism underlying calpain system contribution to such diseases is poorly understood. Our present data suggested that targeting EC calpain systems eliminates VEGF-C deposition in the cells, and it is sufficient for suppressing allograft tumors and OIR (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] Indeed, expression levels of μ-calpain correlate with malignancy in renal cell carcinoma and invasiveness in hepatocellular carcinoma. 28,29 Systemic overexpression of CAST and pharmacological intervention against systemic calpain systems reportedly ameliorate allograft tumors 30 and OIR, 14 respectively; nevertheless, the mechanism underlying calpain system contribution to such diseases is poorly understood. Our present data suggested that targeting EC calpain systems eliminates VEGF-C deposition in the cells, and it is sufficient for suppressing allograft tumors and OIR (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…35 Calpain expression has been correlated with chemotherapeutic resistance in colorectal cancer, esophageal cancer, and melanoma. 21,36,37 This resistance has been specifically correlated with calpain-2 activity. In melanoma, the correlation has been extended to survival outcomes with tumors expressing high levels of calpain-2 resulting in shorter survival for patients.…”
Section: Discussionmentioning
confidence: 96%
“…In melanoma, the correlation has been extended to survival outcomes with tumors expressing high levels of calpain-2 resulting in shorter survival for patients. 37,38 Importantly, calpain proteolytic activity has been shown to increase NFκB signaling in melanoma cancer cells and treatment with calpain inhibitor was able to attenuate this signaling in cisplatin resistant cells. 38 Other researchers have demonstrated a correlation between calpain expression and drug resistant esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This compound can also cause an ERS response in some cells, but this phenomenon has not yet been examined in HSCs. Calpain inhibitors are tetrapeptide acetal protease inhibitors that behave similarly to intracellular endogenous calpain inhibitory proteins by recognizing and specifically binding to conformational features of calpain associated with Ca 2+ binding, thus reducing calpain activity . In the present study, we treated TGF‐β1‐induced HSCs with calcium ionophore A23187 and calpain inhibitor to explore the effect on apoptosis resulting from ERS pathway activation.…”
Section: Discussionmentioning
confidence: 99%